2013
DOI: 10.1681/asn.2012080844
|View full text |Cite
|
Sign up to set email alerts
|

N-WASP Is Required for Stabilization of Podocyte Foot Processes

Abstract: Alteration of cortical actin structures is the common final pathway leading to podocyte foot process effacement and proteinuria. The molecular mechanisms that safeguard podocyte foot process architecture and maintain the three-dimensional actin network remain elusive. Here, we demonstrate that neuronal Wiskott-Aldrich syndrome protein (N-WASP), which promotes actin nucleation, is required to stabilize podocyte foot processes. Mice lacking N-WASP specifically in podocytes were born with normal kidney function b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…1C) (23). As expected, EPB41L5 displayed on a subcellular level a typical FA localization pattern close to the cell border (Fig.…”
Section: Resultssupporting
confidence: 80%
“…1C) (23). As expected, EPB41L5 displayed on a subcellular level a typical FA localization pattern close to the cell border (Fig.…”
Section: Resultssupporting
confidence: 80%
“…As these flies aged, nephrocytes expressing APOL1-G1 became much larger, reaching almost twice the size of the control nephrocytes after 15 days. During this time, however, the number of APOL1-G1-expressing nephrocytes progressively decreased, with concomitant accumulation of cell debris and 54 at normal levels throughout the course of the experiment. LysoTracker fluorescence was lower in nephrocytes expressing APOL1 G0 and G1 at day 1.…”
Section: Discussionmentioning
confidence: 94%
“…The attachment of mock-transfected HEK cells was significantly higher on the uncoated surface compared with the collagencoated surface. There is little information regarding the activity of podosomes in podocytes, but a recent publication reported that N-WASP, a crucial and characteristic regulator involved in the formation of podosomes [20], is also important in maintaining the podocyte foot processes [21]. It indicates that HEK cells, at least in certain experimental conditions, do not attach very well to collagen.…”
Section: Discussionmentioning
confidence: 99%